Hydrological Performance of Way Linti Watershed Based on Discharge Fluctuation Coefficient, Runoff Coefficient, and Sediment Load - Sofyan, Alfi; Yuwono, Slamet Budi; Hilmanto, Rudi; Setiawan, Agus; Safe'i, Rahmat (The University of Lampung, 2024)
The response of the hydrological characteristics of a watershed to rain events is strongly influenced by land cover conditions and topography. The research was carried out in the Way Linti watershed Pesawaran District, Lampung Province. This study aims to learn of hydrological characteristics of Way Linti watershed which is includes the calculation of the discharge fluctuation coefficient (DFC), runoff coefficient (RC) and Sedimentation. The method used in this study refers to the Minister of Forestry Regulation No. 61/2014 concerning Monitoring and Evaluation of Watershed Performance. The data collected includes rainfall, land coverage, river discharge data and sedimentations. The results of the data collection were analyzed to determine the actual condition of hydrological performance of Way Linti watershed. The results of research of the hydrological characteristics of the Way Linti showed that discharge fluctuation coefficient (DFC) of 367.94 which is very high category, runoff coefficient (RC) of 0.193 (very low category), and sediment load (SL) of 58.78 mg/l (very high category). Keywords: Coefficient Runoff, Discharge Fluctuation Coefficient, Sediment Load.